DETECTION OF THE EXISTENCE OF THE OMPK36 GENE ISOLATE KLEBSIELLA PNEUMONIAE BACTERIA PRODUCING EXTENDED SPECTRUM ?-LACTAMASE (ESBL) AT PROF. DR. I.G.N.G. NGOERAH HOSPITAL - Dewi, I Gusti Ayu Candra; Fatmawati, Ni Nengah Dwi; Darwinata, Agus Eka; Pinatih, Komang Januartha Putra (E-Jurnal Medika Udayana; Vol 13 No 10 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i10.P18, 2024)
Infection by multidrug resistant organisms (MDRO) is a global health problem. One example of MDRO is a bacterium that produces Extended Spectrum ?-Lactamase (ESBL), one of which is the bacterium Klebsiella pneumoniae . Klebsiella pneumoniae has several virulence factors and mechanisms of antibiotic resistance. There is a virulence factor which is also a resistance mechanism, namely the presence of the OmpK36 protein which has a dual role. This study aims to determine the presence of the OmpK36 gene in ESBL-producing K. pneumoniae clinical isolates at Prof. Dr. I.G.N.G. Ngoerah using the polymerase chain reaction (PCR) method and calculating the percentage of the presence of the gene. The research method used was observational with a cross-sectional descriptive approach during the period March-September 2022 with a total sampling method using 77 isolates of ESBL-producing K. pneumoniae bacteria for the period December 2021 – April 2022. The research procedure was divided into culture and PCR stages with temperature denaturation 95 0 C, annealing 48 0 C, and extension 72-740 0 C and continued with electrophoresis stages so that the results of 74 samples found the presence of the OmpK36 gene, namely 96.10% and a negative result in the absence of the OmpK36 gene was worth 3 samples (3.9%). The impact of OmpK36 loss events on the surface of the K. pneumoniae structure undergoes remodeling and thereby alters phagocyte binding, leading to increased susceptibility/resistance to phagocytosis, and decreased virulence. Keywords : K. pneumoniae, ESBL, OmpK36 gene